Performance of ancestry-informative SNP and microhaplotype markers. (November 2019) - Cheung, Elaine Y.Y.; Phillips, Christopher; Eduardoff, Mayra; Lareu, Maria Victoria; McNevin, Dennis
Highlights: Microhaplotypes outperform a majority of SNPs for ancestry inference. Rosenberg's informativeness ( I n ) was the most appropriate metric for ranking AIMs. A balance of population-specific markers is appropriate for informative panels. We propose a method to balance AIMs for optimum population differentiation. Abstract: The use of microhaplotypes (MHs) for ancestry inference has added to an increasing number of ancestry-informative markers (AIMs) for forensic application that includes autosomal single nucleotide polymorphisms (SNPs) and insertions/deletions (indels). This study compares bi-allelic and tri-allelic SNPs as well as MH markers for their ability to differentiate African, European, South Asian, East Asian, and American population groups from the 1000 Genomes Phase 3 database. A range of well-established metrics were applied to rank each marker according to the population differentiation potential they measured. These comprised: absolute allele frequency differences ( δ ); Rosenberg's informativeness for (ancestry) assignment ( I n ); the fixation index ( F ST ); and the effective number of alleles ( A e ). A panel consisting of all three marker types resulted in the lowest mean divergence per population per individual (MDPI = 2.16%) when selected by I n . However, when marker types were not mixed, MHs were the highest performing markers by most metrics (MDPI < 4%) for differentiation between the five continental populations.